Mapping the landscape of research on knowledge workers: a bibliometric review - Han, Weijing; Abdrahim, Nur Aira; Iqbal, Aatif; Zakaria, Noor Syamilah; Ghazali, Norliza (Macrothink Institute, 2023)
Knowledge workers remain to be seen as one of the biggest assets for modern enterprises to maintain their competitiveness in the twenty-first century. This has led to a steady increase in academic interest in knowledge workers research, as evidenced by the rise in the number of related publications. However, there is a dearth of research on the growth and existing literary landscape of research focusing on knowledge workers, thus making it challenging for scholars to determine the current trends and future direction in this area. To address the issue, this study provided an overview of the evolution of academic research on knowledge workers over four decades (1981-2021) and identified the existing key trends. A bibliometric review of the data extracted from the Web of Science database using Biblioshiny and VOS viewer. The analysis of 1667 articles confirmed a steady growth in the literature on knowledge workers both in terms of the number of publications and citations. The study identified the evolution of knowledge research in three key dimensions: knowledge work, performance, and human capital. Moreover, “performance”, “management” and “model” have also become the most frequently occurring words. The research findings not only deepened our comprehension of the research landscape but also provided insights into potential implications.